The design and control of a therapeutic exercise robot for lower limb rehabilitation: Physiotherabot - Akdoğan, Erhan; Adli, Mehmet Arif (Mechatronics (Oxford), 2011)
This study explains the design and control of three degrees of freedom therapeutic exercise robot (Physiotherabot) for the lower limbs of a patient who needs rehabilitation after a spinal cord injury (SCI), stroke, muscle disorder, or a surgical operation. In order to control this robot, a “Human–Machine Interface” with a rule-based control structure was developed. The robot manipulator (RM) can perform all active and passive exercises as well as learn specific exercise motions and perform them without the physiotherapist (PT) through the Human–Machine Interface. Furthermore, if a patient reacts against the robot manipulator during the exercise, the robot manipulator can change the position according to feedback data. Thus, the robot manipulator can serve as both therapeutic exercise equipment and as a physiotherapist in terms of motion capability. Experiments carried out on healthy subjects have demonstrated that the RM can perform the necessary exercise movements as well as imitate the manual exercises performed by the PT.